1999
DOI: 10.1001/archpsyc.56.12.1127
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Eye Tracking Deficits in First-degree Relatives of Schizophrenic Patients

Abstract: Subtle frontal dysfunction seems to be a pathophysiological substrate of ETD in relatives of schizophrenic patients, and may be one aspect of genetically mediated differences in brain function relevant to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 66 publications
6
29
0
Order By: Relevance
“…However, it has been reported that smooth pursuit quality (measured by pursuit gain or catch-up saccade rate) is significantly associated with measures of frontal structural integrity (Bagary et al, 2004) and frontal activation in schizophrenic patients (Ross et al, 1995;Hong et al, 2005;Keedy et al, 2006) and unaffected relatives (O'Driscoll et al, 1999). Although the PhysAn group did tend towards poorer pursuit gain, the small number of subjects made these results insignificant here.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, it has been reported that smooth pursuit quality (measured by pursuit gain or catch-up saccade rate) is significantly associated with measures of frontal structural integrity (Bagary et al, 2004) and frontal activation in schizophrenic patients (Ross et al, 1995;Hong et al, 2005;Keedy et al, 2006) and unaffected relatives (O'Driscoll et al, 1999). Although the PhysAn group did tend towards poorer pursuit gain, the small number of subjects made these results insignificant here.…”
Section: Discussionmentioning
confidence: 58%
“…Eye movements were monitored using an Eyelink infrared video-based tracking system (SR Research, Mississauga, Canada) and data were analyzed with custom software (Holahan and O'Driscoll, 2005). The dependent measure was peak pursuit gain, a measure previously found to be correlated with frontal activation (O'Driscoll et al, 1999) and frontal structural integrity (Bagary et al, 2004). Pursuit gain was compared across groups with a one-way ANOVA.…”
Section: Psychological and Physiological Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…While eye-tracking deficits may involve frontal lobe function, 43 other measures of prefrontal function (eg working memory subscales of the WISC, eg digit span) did not show association. While most of the SNPs tested revealed a positive association with increased frontal gray matter volume loss on MRI over time, one SNP, M03, also showed a positive association with eye-tracking dysfunction and a measure of premorbid functioning, which covers areas such as school, social, speech, and motor delays and difficulties.…”
Section: Discussionmentioning
confidence: 71%
“…In a preliminary study, the authors have observed reduced activation in prefrontal brain regions in HR adolescents during a spatial working memory task [50]. Preliminary fMRI studies have shown that performance on these tasks of eye-movement control and working memory in these subjects result in aberrant fMRI-measured activation in the frontal and parietal regions of the brain [51] and the frontal eye fields, which are thought to regulate eye movement control [52]. Studies have shown that the response of the prefrontal cortex in adult relatives is similarly inefficient to increases in working memory demands [49], providing a measure of convergence with fMRI results of child and adolescent relatives.…”
Section: Functional Magnetic Resonance Imaging Studiesmentioning
confidence: 96%